2017
DOI: 10.1016/j.bbagen.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the selective binding of antibiotics vancomycin and teicoplanin by the VanS receptor regulating type A vancomycin resistance in the enterococci

Abstract: A-type resistance towards “last-line” glycopeptide antibiotic vancomycin in the leading hospital acquired infectious agent, the enterococci, is the most common in the UK. Resistance is regulated by the VanRASA two-component system, comprising the histidine sensor kinase VanSA and the partner response regulator VanRA. The nature of the activating ligand for VanSA has not been identified, therefore this work sought to identify and characterise ligand(s) for VanSA. In vitro approaches were used to screen the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 79 publications
(107 reference statements)
1
46
1
Order By: Relevance
“…Experimental evidence for this model has been provided in a study that used biophysical approaches such as analytical ultracentrifugation and near‐UV circular dichroism (CD) to monitor the changes in oligomerization and conformation of detergent‐solubilized VanS A in the presence of vancomycin . Another study further supported this model demonstrating that vancomycin induced significant thermostability and conformational changes in purified VanS A, while other potential signals such as the peptidoglycan components Ala‐ d ‐γ‐Glu‐Lys‐ d ‐Ala‐ d ‐Ala, N ‐acetylmuramic acid or d ‐Ala‐ d ‐Ala had no such effect . However, other studies contested this model, reporting the lack of a VanS A ‐vancomycin complex even at high concentrations of vancomycin and suggesting that the enzymatic activities of detergent or amphipol‐solubilized VanS A are not altered in the presence of vancomycin .…”
Section: Vancomycin Resistance Mechanisms: Two Main Routes For Modifimentioning
confidence: 94%
See 1 more Smart Citation
“…Experimental evidence for this model has been provided in a study that used biophysical approaches such as analytical ultracentrifugation and near‐UV circular dichroism (CD) to monitor the changes in oligomerization and conformation of detergent‐solubilized VanS A in the presence of vancomycin . Another study further supported this model demonstrating that vancomycin induced significant thermostability and conformational changes in purified VanS A, while other potential signals such as the peptidoglycan components Ala‐ d ‐γ‐Glu‐Lys‐ d ‐Ala‐ d ‐Ala, N ‐acetylmuramic acid or d ‐Ala‐ d ‐Ala had no such effect . However, other studies contested this model, reporting the lack of a VanS A ‐vancomycin complex even at high concentrations of vancomycin and suggesting that the enzymatic activities of detergent or amphipol‐solubilized VanS A are not altered in the presence of vancomycin .…”
Section: Vancomycin Resistance Mechanisms: Two Main Routes For Modifimentioning
confidence: 94%
“…51 Another study further supported this model demonstrating that vancomycin induced significant thermostability and conformational changes in purified VanS A, while other potential signals such as the peptidoglycan components Ala-D-γ-Glu-Lys-D-Ala-D-Ala, N-acetylmuramic acid or D-Ala-D-Ala had no such effect. 52 However, other studies contested this model, reporting the lack of a VanS A -vancomycin complex even at high concentrations of vancomycin and suggesting that the enzymatic activities of detergent or amphipol-solubilized VanS A are not altered in the presence of vancomycin. 50 A possible explanation of the contradictory results of these latter studies can be due to the VanS A solubilization using detergents, which are known to affect the function of sensor kinase membrane proteins.…”
Section: Vans Sensor Kinasementioning
confidence: 99%
“…In VRE A, GPA resistance is induced by GPAs as well as other non-structurally related cell wall inhibitors, such as moenomycin (26). The broad structural diversity of the compounds that trigger VanS A supports the second hypothesis, but recently in vitro studies have demonstrated binding of VanS A to teicoplanin and vancomycin (27). Since VanS B only responds to vancomycin-type GPAs but not teicoplanin, VanS B may bind directly to the GPA, since cell wall intermediates would be built up in both vancomycin and teicoplanin treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Analysis of the variation of M w with loading concentration revealed dissociation constants in the range 25-75 µM, commensurate with a relatively weak association. That study 4 , alongside companion studies 6,7 , also demonstrated a weak interaction with the A-type bacterial VanS histidine protein kinase involved in the activation of vancomycin resistance, at least in aqueous solution.…”
mentioning
confidence: 84%